Cenostigma tocantinum, a new host of Colletotrichum siamense - Ferreira e Ferreira, Ana Francisca Tibúrcia A.; Silva, Blenda N. S.; Mota, Adolfo J.; Lima, Jânia Lília S. B. (Forest pathology = Journal de pathologie forestière = Zeitschrift für Forstpathologie, 2020)
Trees of Cenostigma tocantinum showing brown leaf spots surrounded by chlorotic areas were observed at the campus of the Federal University of Amazonas, Brazil, in 2018. Necrotic lesions were covered by orange masses of hyaline cylindrical conidia with rounded ends, typical of the genus Colletotrichum. Three monoconidial isolates were subject of DNA extraction followed by PCR amplification and sequencing of the ribosomal internal transcribed spacer (ITS rDNA), beta‐tubulin 2 (TUB2) and glycerol‐3‐phosphate dehydrogenase (GAPDH) genes. Multilocus phylogenetic analyses and morphological characterization allowed the identification of the isolates as C. siamense, a member of the C. gloeosporioides species complex. The pathogenicity of C. siamense was confirmed, and Koch's postulates completed. This is the first worldwide report of C. siamense causing leaf spots on Ce. tocantinum.